Relationships of business strategies and organizational characteristics with innovation types: application in service companies - Ostos Mariño, Jhony (2019)
Various authors maintain that innovation practices depend on business strategies, therefore companies must configure an organizational structure that facilitates the coordination of tasks and allows objectives to be reached. In a sample of 203 service companies, an analysis was carried out of the influence of business strategies and organizational characteristics on technical innovation and administrative innovation. The results indicate that there is an important relationship between the business strategy and the technical and administrative innovations. On the other hand, organizational characteristics only had a significant relationship with technical innovation but not with the administrative innovation.